Family functioning in the aftermath of a natural disaster - McDermott Brett M; Cobham Vanessa E (BMC Psychiatry, 2012)
Abstract Background Increased understanding of the complex determinants of adverse child mental health outcomes following acute stress such as natural disasters has led to a resurgence of interest in the role of parent psychopathology and parenting. The authors investigated whether family functioning in the post-disaster environment would be impaired relative to a non-exposed sample and potential correlates with family functioning such as disaster-related exposure and child posttraumatic mental health symptoms. Methods Three months after a category 5 tropical cyclone that impacted north Queensland Australia, school-based screening was undertaken to case identify children who may benefit from a mental health intervention. Along with obtaining informed consent, parents completed a measure of family functioning. Results Of 145 families of children aged 8 to 12 years, 28.3% met criteria for dysfunction on the Family Adjustment Device, double the frequency in a community sample. The dysfunction group was significantly more likely to have experienced more internalising (anxiety/depression) symptoms. However, in an adjusted logistic regression model this group were not more likely to have elevated disaster-related exposure nor did children in these families validate more PTSD symptoms. Conclusions The implications of post-disaster discordant family functioning and possible different causal pathways for depressive and PTSD-related symptomatic responses to traumatic events are discussed.